Dirty work in the clean city: An embodied Urban Political Ecology of women informal recyclers' work in the 'clean city'. (June 2023) - Wittmer, Josie
This paper investigates the ways that 'cleaning up' Indian cities impacts those who rely on accessing waste on city streets for their livelihoods. I focus on low-income Dalit women recyclers in Ahmedabad, India as they navigate material and discursive shifts in urban waste management emanating from the national Swachh Bharat Abhiyan and 2016 Solid Waste Management Rules, and the municipal privatization and mechanization of solid waste management practice. The study is informed by 10 months of ethnographic research and a series of interviews and group discussions with women recyclers between 2016 and 2018. Using a feminist embodied Urban Political Ecology approach, I suggest the imagining and production of the 'clean and green' world-class city is affecting Dalit women recyclers' work in two ways. First, I argue that emerging cleanliness governance mechanisms and solid waste management practices are re-spatializing and masculinizing waste labour in the city. I show how spatial, discursive and temporal shifts in solid waste management are producing new challenges for Dalit women recyclers in accessing waste, intensifying their physical and financial burdens and requiring more precarious adaptations to generate daily incomes. Second, I explore women recyclers' own clean city aspirations, expressing a desire to experience the 'clean and green' city and a simultaneous sense of betrayal as their livelihoods, communities and bodies are excluded from its imagining and material production. I suggest that an embodied intersectional analysis of waste labour reveals how the imagining and production of clean and sustainable 'modern' cities can cause damage to socially marginalized and gendered bodies as they are displaced from work and denied the substantive experience of urban citizenship in the 'world-class' city. Attention to embodiment thus deepens an understanding of the complexities and contradictions invoked in urban environmental governance and infrastructural transformations, informing the imagining and production of more equitable and reparative urban futures.